Influence of expansion level on base pressure and reattachment length - Pathan, Khizar Ahmed; Dabeer, Prakash S; Khan, Sher Afghan (Penerbit Akademia Baru, 2019)
In high-speed projectiles like a rocket, the thrust is created by the convergent-divergent nozzle. The flow from the nozzle is exhausted in the enlarged duct of larger diameter to maximize the thrust. When the flow from the nozzle is exhausted in the enlarged duct, the base pressure gets reduced and hence increases base drag. This paper numerically simulates and investigates the flow field and the effectiveness of the Nozzle Pressure Ratio (NPR) on the base pressure, development of the flow field in the enlarged duct, the location of reattachment point, and the reattachment length. The supersonic flow was generated by the C-D nozzle, and the same is exited in the enlarged duct of area ratio 4.84 (ratio of enlarged duct area to nozzle exit area). The base pressure and the wall pressure distribution along the enlarged duct length have been studied. The Mach numbers considered for CFD analysis are 1.5, 2.0 and 2.5. NPR and the L/D ratios of the study are from 2, 5, and 8. Based on the results it is concluded that with enhancement in NPR, the nozzle becomes under-expanded, the reattachment length is reduced and the base pressure tends to get reduced at all the parameters of the present investigation.